Training on Problem-Solving Learning Strategies for Special Education Teachers in Teaching Mathematics to People with Dyscalculia in Kab. Garut - Sundayana, Rostina; Afriansyah, Ekasatya Aldila; Maryati, Iyam; Puspitasari, Nitta; Sumiarelati, Sumia; Hadiansyah, Nirwan (Fakultas Kewirausahaan Universitas Garut, 2023)
Although the implementation of the National Assessment policy has been running for one year, it is suspected that the understanding of teachers, parents and students about the National Assessment is not sufficient. The results of the situation analysis on the understanding of teachers at PLB teachers Kab Garut regarding minimum competency assessments show that (1) teachers' understanding of AN is still low and (2) the ability of teachers to prepare problem solving-based questions is still low. The solution agreed upon with partners is to optimize learning by training and assisting teachers in developing problem solving questions. The target audience is 16 teachers at Guru PLB Kab Garut. The method of implementing the activity is the participatory rural appraisal model, the technology transfer model, and training. The results of the activity show that there has been an increase in teachers' understanding of the problem solving questions with an average score of 76. A total of 62.5% of the training teachers have also succeeded in developing their own problem solving questions in accordance with the guidelines.